We Teach Art, but Can Art Teaches Us? John Dewey on the Significance of Art - D. Rio Adiwijaya (Graduate School of Institut Seni Indonesia Yogyakarta, 2019)
AbstractThose who pursue a teaching career in art and design are most likely aware of one of its pressing dilemmas. On the one hand, as a subject situated in the postindustrial higher education setting where the progressive accumulation of knowledge – mostly in propositional form and explaining how things work in physical or social reality – constitutes its main purpose, art are unavoidably driven to adopt the same objective. On the other hand, most artistic activities are not aimed to produce and derived from replicable research propositions but conducted to generate novel artifacts, performances, narratives or experiences in order to enhance artistic universe. Regarding their being as artifactual, non-propositional and idiosyncratic, artworks are unfortunately regarded as mere products of subjective emotions, where it’s appropriate roles are nothing more than spectacles, entertainments or ornaments, which at the same time testify its marginal relationship with knowledge. However, this predicament is not as self-evident as it looks since it is in fact resulted from a particular philosophical outlook, namely, an outlook that bifurcates mind and body, rational and emotional, subject and object, and so forth that comes down to us from the Platonic and Cartesian tradition. It is precisely the thought of John Dewey that profitably conceives art prior to Platonic/Cartesian bifurcation which will be discussed in this paper. Art, for Dewey, is not a product of a mere subjectivity, but instead emerges from “experience,” understood as primary, pre-linguistic (hence pre-dualism) and embodied human-environment “transactions.” Located in such a primary domain, art regains its utmost significance. AbstrakMereka yang mengejar karir dosen di bidang seni dan desain kemungkinan besar menyadari salah satu dilemanya yang mendesak. Di satu sisi, sebagai bidang yang berada dalam lingkungan pendidikan tinggi pasca-industri di mana akumulasi pengetahuan progresif - kebanyakan dalam bentuk proposisional dan menjelaskan bagaimana hal-hal bekerja dalam realitas fisik ataupun sosial - merupakan tujuan utamanya, seni secara tidak terhindarkan didorong untuk mengadopsi tujuan yang sama. Di sisi lain, sebagian besar kegiatan artistik tidak bertujuan untuk menghasilkan, dan berasal dari proposisi penelitian yang dapat direplikasi namun dilakukan untuk menghasilkan artefak, performa, narasi atau pengalaman baru dalam rangka mengembangkan semesta artistik. Melihat keberadaan seni yang serba artifaktual, non-proposisional dan unik, karya seni dianggap sebagai semata-mata produk dari emosi subjektif, di mana perannya dianggap tidak lebih dari tontonan, hiburan atau ornamen, yang pada saat yang sama menyiratkan hubungannya yang marginal dengan pengetahuan. Namun, dilema ini bukan sesuatu yang sudah jelas dengan sendirinya, karena nyatanya dihasilkan dari pandangan filosofis tertentu, yaitu, pandangan yang membelah tajam antara pikiran dan tubuh, rasional dan emosional, subjek dan objek, dan sebagainya yang diturunkan pada kita dari tradisi Platonis dan Cartesian. Adalah pemikiran proseni dari John Dewey yang bergerak sebelum bifurkasi Platonis/Cartesian yang akan dibahas dalam makalah ini. Seni, bagi Dewey, bukan produk dari subjektivitas belaka, melainkan muncul dari